TRANS URETHRAL ELECTRIC VAPORISATION OF PROSTATE AS AN ALTERNATE TO TRANS URETHRAL RESECTION IN BENIGN PROSTATIC HYPERPLASIA - Akhtar, Malik Masood; Orakzai, Nasir; Qureshi, Abdul Manan (Journal of Ayub Medical College Abbottabad, 2004)
Background: There is an impression that trans urethral electric vaporisation of prostate (TUEVP) is a relatively safe surgical procedure for obstructing benign prostates; however before considering it an alternative to Trans urethral resection (TURP) in our setting, we conducted this study to assess its safety, convenience and especially cost effectiveness in our practice. Methods: Fifty patients with signs of benign prostatic enlargement causing acute urinary retention were selected and divided into two equal groups A and B. Patients of group A underwent TURP while the group B patients had TUEVP. Postoperative follow up to assess the results of the surgeries, including noting the complication rate, began 24 hour after the catheter was removed, continuing during postoperative visits of the patient at 2 weeks, 3 months and finally 6 months. Results: For approximately same size prostate, the mean operation time was less for TUEVP as compared to the TURP. The mean volume of irrigating fluid used and the number of blood transfusions required was also less in the TUEVP patients. In addition, TURP patients were also noted to have slight postoperative hyponatraemia. Clot retention was more frequent in the TURP group than the TUEVP group. Urethral catheters were required for longer duration (mean duration 74.88 hrs vs 24hrs, p=0.0001) and so was the hospital stay (mean duration 6.25 days vs 4.4 days, p=0.0046) in the TURP group patients. Total mean cost of treatment was also higher in the patients undergoing TURP. Among the complications, only the peroperative blood transfusion rate was higher in the TURP patients as noted above. Conclusions: The TURP has slightly higher morbidity and is costlier than TUEVP but its results in terms of relieving outflow obstruction are significantly better than TUEVP. It is therefore concluded that TURP is a more effective procedure but TUEVP with lesser morbidity and cost, is more suitable for relatively lesser obstructions in our setting. Key Words: Prostate, Prostatectomy, Diathermy